Acceptance of the HPV Vaccine in a Multiethnic Sample of Latinx Mothers. (February 2021) - Lindsay, Ana Cristina; Valdez, Madelyne J.; Delgado, Denisse; Restrepo, Emily; Guzmán, Yessica M.; Granberry, Phillip
This descriptive qualitative study explored Latinx mothers' acceptance of the human papillomavirus (HPV) vaccine for their adolescent children. Data were collected through individual, semi-structured interviews and analyzed using a hybrid method of thematic analysis that incorporated deductive and inductive approaches. Twenty-two ( n = 22), mostly foreign-born, Latinx mothers of male and female adolescents participated in the study. Three main themes and nine subthemes emerged from the analyses. Findings identified the need for increased efforts to raise awareness and knowledge among Latinx mothers of the direct benefits of the HPV vaccine for sons, including stressing prevention of HPV-associated cancers in males. Findings also underscore the need for improved health care providers' communication and recommendation of the HPV vaccine for Latinx adolescent males. Future research should intervene upon the study's findings to address barriers that remain and affect Latinx mothers' acceptance and uptake of the HPV vaccine for their children, in particular their sons.